Dietary Diversity and Iron Status in Pregnant Women Attending the Antenatal Clinic at Narok County Referral Hospital, Kenya - Adan, Sahara Ibrahim; Chege, Peter; Bor, Wesley (African Journal of Nutrition and Dietetics, 2023)
Dietary diversity is widely acknowledged as a fundamental factor influencing the iron status of pregnant women. Iron deficiency anemia constitutes a pervasive nutritional concern on a global scale, particularly during pregnancy, and it is linked to an array of adverse consequences such as prenatal mortality, low birth weight, preterm birth, and intrauterine growth retardation. Despite this recognition, there exists a notable gap in our understanding of the dietary habits and iron status of pregnant women attending the antenatal clinic at Narok County Referral Hospital, Kenya. To address this gap, we conducted a cross-sectional study, targeting a cohort of 178 pregnant women receiving antenatal care at the aforementioned hospital. The study used a cross-sectional study design with a target population of 178 pregnant mothers attending the antenatal clinic (ANC) in Narok County Referral Hospital, Kenya. A researcher-administered questionnaire, focus group discussion guides (FGD), and key informant interviews (KII) were used to collect data. Logistical regression and Odds ratio were used to control for other factors that affect iron status, and the Odds ratio was used to determine the likelihood of iron deficiency as influenced by dietary diversity. The results revealed that a significant proportion of the pregnant women were aged between 18-24 years (44.4%), were married (71.3%), and engaged in small businesses (52.2%). Approximately one-third of the participants had two children, with 25.3% having had four live births. The majority (68%) reported consuming four meals daily, but the nutrient intake of pregnant mothers generally fell below-recommended levels, with 57.9% failing to meet the minimum dietary diversity score for women. A considerable portion (62.4%) exhibited normal nutritional status, while 68.5% were under Iron Folic Acid Supplementation (IFAS); however, adherence to the supplementation regimen was poor. Moreover, 52.2% had hemoglobin levels below 12g/dl, indicating a potential issue with iron deficiency. This study uncovered significant demographic characteristics among pregnant women, particularly noting a significant presence of young, married individuals engaged in small-scale businesses. The dietary patterns highlighted a prevalent intake of four meals, but nutrient intake often fell short of recommended levels. Alarmingly, a substantial percentage exhibited low hemoglobin levels, underscoring the critical necessity for improved nutritional interventions. Specifically, enhancing iron supplementation and promoting dietary diversity is imperative to address the potential risk of iron deficiency among this vulnerable population.